PSYCHOLOGICAL CULTURE OF A TEACHER-COACH AS THE BASIS FOR SUCCESSFUL COACHING YOUNG ATHLETES - Inna S. Kochergina; Natalia E. Serebrovskaya; Sergey I. Timin; Tamara T. Shelina (Russian Journal of Education and Psychology, 2022)
Purpose. The article is concerned with the theoretical and empirical study of such a complex and at the same time pivotal phenomenon of personality as the psychological culture of a teacher-coach. This phenomenon is considered as the basis of successful coaching training activities of a teacher-coach with young athletes. This article presents an analysis and review of the leading approaches to the understanding of the content of psychological culture within the framework of academic psychology studies, as a result a lack of consistency in the interpretation of the definition of ‘psychological culture’ and its role in the professional development of a teacher-coach are revealed.